2021
DOI: 10.5851/kosfa.2021.e42
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Modified Casein to Whey Protein Ratio on Dispersion Stability, Protein Quality and Body Composition in Rats

Abstract: The present study was designed to investigate the effects of protein formula with different casein (C) to whey protein (W) ratios on dispersion stability, protein quality and body composition in rats. Modification of the casein to whey protein (CW) ratio affected the extent of protein aggregation, and heated CW-2:8 showed a significantly increased larger particle (>100 μm) size distribution. The largest protein aggregates were formed by whey protein self-aggregation. There were no significant differences in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Nevertheless, the CW ratio did not show a significant difference in growth performance among the milk-administered groups. Similarly, in our previous study, we reported that different CW compositions of the experimental diet did not alter body weight and weight gain [ 20 ]. Additionally, Yajima et al demonstrated that body weight gain did not change with CW ratio in rats [ 29 ].…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Nevertheless, the CW ratio did not show a significant difference in growth performance among the milk-administered groups. Similarly, in our previous study, we reported that different CW compositions of the experimental diet did not alter body weight and weight gain [ 20 ]. Additionally, Yajima et al demonstrated that body weight gain did not change with CW ratio in rats [ 29 ].…”
Section: Resultssupporting
confidence: 69%
“…The increased viscosity or firmness of the coagulant was observed as the ratios changed from CW0:10 to CW8:2 [ 41 ]. Our previous study’s findings also showed that CW2:8 significantly increased true digestibility compared to CW10:0, CW8:2, and CW5:5 in rats [ 20 ]. In contrast to previous studies, we observed no significant difference in the true digestibility among all groups.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Milk protein comprises 80% casein protein, and 20% whey protein and has been shown to effectively enhance gastrointestinal activity, function and immunity (Maldonado Galdeano et al 2011;Pezeshki et al 2015). Whey protein is more effective than casein protein in reducing food intake, weight and fat gain, and improving glucose tolerance (Jeong et al 2021). The whey protein comprises several bioactive fractions, including glycomacropeptide, β-lactoglobulin, αlactalbumin and lactoferrin, which decrease body weight and fat content (Pezeshki et al 2015).…”
Section: Introductionmentioning
confidence: 99%